Stages of Formation and Development of Cartographic Research at the Institute of Geography of the NAS of Ukraine - Бочковська, А. І.; Bochkovska, A. I. (Ukrainian Geographical Journal, 2024)
The article presents a retrospective view of the Department of Cartography’s cartographic research over 60 years of its operation. The main scientific directions of research, in accordance with the then-existing concepts of the development of science in NASU, cartographic scientific concepts, and the demands of public practice, are highlighted. Based on research, the main stages of the development of geographical cartography at the Institute of Geography are identified, and their filling with research topics and scientific and practical results is highlighted. Three periods of development of geographical cartography were recorded: 1964–1970—formation of the department and execution of works on individual requests of the company; 1971–1990—development of methodological directions of cartographic research and their practical implementation; 1991–2024—the development of cartographic works (individual thematic maps, complex and thematic atlases, the development of interactive mapping, the development and publication of the National Atlas of Ukraine) was carried out from some promising regions and their research.